2021
DOI: 10.21886/2308-6424-2021-9-2-111-124
|View full text |Cite
|
Sign up to set email alerts
|

Urinary fistulas after partial nephrectomy in renal cell carcinoma

Abstract: Urinary fistulas after partial nephrectomy are rare complications of this operation. There are various reasons for their development, prevention and treatment. This review analyzes the results of the cases' prevalence of urine leakage after partial nephrectomy with various approaches, occurrence's predictors of urinary fistulas, possible ways of their intraoperative prevention and treatment methods. The obtained data show that the size of tumors, their endophytic nature and proximity to the kidney pelvicalycea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 75 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…In the review of Guliev, frequency of urinary fistula after partial nephrectomy was reported to be 0.25-17% [1]. He also reported that urinary fistula occurred less often in endoscopic surgery especially with robot assistance than in open surgery, of which he speculated attribution of patient selection, better visualization, and secure suture in robot surgery [1]. Most cases of urinary fistula are diagnosed by prolonged drainage and in minor cases the diagnosis is made after removal of perisurgical drainage [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the review of Guliev, frequency of urinary fistula after partial nephrectomy was reported to be 0.25-17% [1]. He also reported that urinary fistula occurred less often in endoscopic surgery especially with robot assistance than in open surgery, of which he speculated attribution of patient selection, better visualization, and secure suture in robot surgery [1]. Most cases of urinary fistula are diagnosed by prolonged drainage and in minor cases the diagnosis is made after removal of perisurgical drainage [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple related factors for urinary fistula after partial nephrectomy have been raised previously, including tumor size, endophyticity, proximity to the collecting system or sinus, intrarenal pelvis, RENAL nephrometry score, renorrhaphy, repair of the collecting system, blood loss, warm ischemic time, surgical time, severity of chronic kidney disease, surgeon's experience, and so on [1][2][3][4][5][6]. In the present case, the tumor was completely endophytic and large at 35 mm in diameter with a higher RENAL nephrometry score of nine, suggesting a higher risk of urinary fistula.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations